Sustained Water Storage in Horn of Africa Drylands Dominated by Seasonal Rainfall Extremes. Issue 21 (4th November 2022) - Adloff, Markus; Singer, Michael Bliss; MacLeod, David A.; Michaelides, Katerina; Mehrnegar, Nooshin; Hansford, Eleanor; Funk, Chris; Mitchell, Daniel
Abstract: Rural communities in the Horn of Africa Drylands (HADs) are increasingly vulnerable to multi‐season droughts due to the strong dependence of livelihoods on seasonal rainfall. We analyzed multiple observational rainfall data sets for recent decadal trends in mean and extreme seasonal rainfall, as well as satellite‐derived terrestrial water storage and soil moisture trends arising from two key rainfall seasons across various subregions of HAD. We show that, despite decreases in total March‐April‐May rainfall, total water storage in the HAD has increased. This trend correlates strongly with seasonal totals and especially with extreme rainfall in the two dominant HAD rainy seasons between 2003 and 2016. We further show that high‐intensity October‐November‐December rainfall associated with positive Indian Ocean Dipole events lead to the largest seasonal increases in water storage that persist over multiple years. These findings suggest that developing groundwater resources in HAD could offset or mitigate the impacts of increasingly common droughts. Plain Language Summary: Over the last 40 years droughts are occurring more often in the Horn of Africa because of less rainfall during rainy seasons. We used satellite data to understand how rainfall has changed and how much water is stored on and below the land surface. We found that water storage is increasing, despite the poor rainy seasons. This is because heavy rain showers have become more common, which can most effective refill the water stored in the ground. Key Points: Rising terrestrial water storage in Horn of Africa Drylands Increasing high‐intensity rainfall events, particularly during October‐November‐December season Terrestrial water recharge correlates with seasonal high‐intensity rainfall